(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2026)
This article examines the ontological status of the human being and the hierarchy of existence in the philosophy of Ibn Sino (Avicenna). The study aims to clarify how the human being is situated within Avicenna’s metaphysical system, particularly in relation to the distinction between necessary and contingent existence, the doctrine of essence and existence, and the gradational structure of being. Special attention is given to the human soul as an immaterial substance, its relation to the body, and its epistemological and moral capacities. The research employs historical-philosophical analysis, comparative methodology, and conceptual reconstruction of primary sources, including Avicenna’s major metaphysical works. The article argues that in Avicenna’s ontology, the human being occupies an intermediate but privileged position within the cosmic order: ontologically contingent yet oriented toward intellectual perfection through conjunction with the Active Intellect. The hierarchy of existence from the Necessary Existent to separate intellects and the sublunary world provides the framework within which human self-realization and moral development become metaphysically grounded.